EFFECT OF PRE-NATAL INTERMITTENT MONOTONOUS AND RHYTHMIC AUDITORY EXPOSURES ON BRAINSTEM NUCLEI PLASTICITY OF ONE DAY-OLD CHICK - Dodik Nursanto; Isabella Kurnia Liem; Ahmad AuliaJusuf; Deswaty Furqonita (Biomedika, 2023)
ABSTRACT Environmental auditory exposure in a form of both enrichment and stressor environmental can differently modulate the development of auditory system Prenatal chronic noise exposure caused neurogenesis and neuroplasticity disorders in the brain's auditory pathway resulting in neurocognitive impairment. Meanwhile exposure to prenatal music positively modifies morphological and biochemical developments in the brain's auditory pathway that supports neurogenesis and neuroplasticity. This study aimed to determine the plasticity of brainstem nuclei after exposure to music, noise, and a combination of both. This research used an experimental method using 24 female chicks as subjects. Subjects were obtained from eggs after incubation, which were divided into 4 groups: control, music, noise, and combined noise and music. Brain stem nuclear plasticity was measured by total number of nuclei, neuronal nuclear area, and synaptophysin expression as parameters. Prenatal music exposure significantly increased the total number of neurons, neuronal nuclear area, and synaptophysin expression in brain stem nuclei (p < 0.001), whereas combined and noise exposure significantly decreased these three plasticity parameters (p < 0.001). In conclusion, prenatal music exposure potential to increase neuroplasticity of brainstem nuclei for better neurocognitive function ABSTRAK Paparan pendengaran lingkungan dalam bentuk enrichment dan stresor lingkungan dapat memodulasi perkembangan sistem pendengaran secara berbeda. Paparan kebisingan kronis prenatal menyebabkan gangguan neurogenesis dan neuroplastisitas pada jalur pendengaran otak sehingga mengakibatkan gangguan neurokognitif. Sementara itu, paparan musik prenatal secara positif mengubah perkembangan morfologi dan biokimia pada jalur pendengaran otak yang mendukung neurogenesis dan neuroplastisitas. Penelitian ini bertujuan mengetahui plastisitas nucleus batang otak setelah paparan musik, kebisingan, dan kombinasi keduanya. Penelitian ini menggunakan metode eksperimen dengan menggunakan 24 ekor anak ayam betina sebagai subjeknya. Subjek diperoleh dari telur setelah diinkubasi, yang terbagi dalam 4 kelompok: kontrol, musik, kebisingan, dan gabungan kebisingan dan musik. Plastisitas nukleus batang otak diukur dengan parameter jumah total nukleus, luas neuronal nuclear area, dan ekpresi synaptophysin. Paparan musik prenatal meningkatkan jumlah total neuron, luas neuronal nuclear area, dan ekspresi synaptophysin di inti batang otak secara signifikan (p< 0,001), sedangkan paparan bising dan kombinasi secara signifikan menurunkan ketiga parameter plastisitas tersebut (p < 0.001). Kesimpulannya, paparan musik prenatal berpotensi meningkatkan neuroplastisitas inti batang otak untuk fungsi neurokognitif yang lebih baik